Identification of anti‐inflammatory active ingredients from Tumuxiang by ultra‐performance liquid chromatography/quadrupole time‐of‐flight‐MSE. (1st February 2018) - Gao, Xia; Ma, Yuling; Wang, Zhuowei; Bia, Ruibin; Zhang, Pei; Hu, Fangdi
Abstract: The dried roots of Inula helenium L. (IH) and Inula racemosa Hook f. (IR) are used commonly as folk medicine as 'tumuxiang' (TMX). The mixing and sharing of IH and IR in clinical use is a universal phenomenon. Modern pharmacological studies confirmed that IH and IR display anti‐inflammatory activities. However, the difference in anti‐inflammatory pharmacodynamic substances between these two herbs is still unknown. In the present study, the fingerprints of 18 IH and nine IR samples were established using UPLC/QTOF‐MS E . A dimethylbenzene‐induced mouse ear vasodilation model was applied in evaluating the anti‐inflammatory properties of all 27 samples. Then, the spectrum–efficacy model between chemical characteristic peaks and anti‐inflammatory activities was investigated using principal component regression and partial least squares. Finally, the combination of UNIFI Scientific Information System with a library search of traditional Chinese medicines was employed to automatically characterize the peaks. UNIFI identified a total of 80 chemical components. Among the components, the 53 characteristic peaks showed correlation with anti‐inflammatory activities, pointing to phenolic and organic acids as primary anti‐inflammatory ingredients of TMX. This approach can efficiently and intelligently facilitate the identification of bioactive components from traditional Chinese medicine.